Strategi Madrasah dalam Meningkatkan Daya Saing Pendidikan Islam di Era Modern: MA Matholi'ul Huda Bugel - Muhammad Abid Robiun Nuha; Sukarman; Mustaqim (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2026)
The development of the modern era and increasingly intense competition among educational institutions require madrasahs to improve the quality of education in order to remain competitive and attractive to society. Madrasahs are not only expected to preserve Islamic values but also to adapt to the advancement of science and technology. This study aims to analyze madrasah strategies in improving the competitiveness of Islamic education through a case study at MA Matholi’ul Huda Bugel, Jepara. The research employed a descriptive qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews, and documentation studies. The research informants consisted of the principal, vice principals, teachers, educational staff, and students selected using purposive sampling techniques. Data analysis was conducted using the Miles and Huberman model through data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The results showed that strategies to enhance the competitiveness of Islamic education were implemented through: 1) improving learning quality using innovative methods; 2) developing teacher competencies through training and academic supervision; 3) strengthening religious culture through habituation of religious activities; 4) utilizing information technology in learning processes; and 5) developing flagship programs, particularly Tahfidz Al-Qur’an and student achievement coaching. Supporting factors included visionary leadership of the principal, collaboration among madrasah members, and parental support. Meanwhile, the obstacles faced included limited infrastructure, technological developments, and the heterogeneous abilities of students.